End-to-end security in embedded system for modern mobile communication technologies - D. Venu; Babu J; R. Saravanakumar; Ricardo Fernando Cosio Borda; Yousef Methkal Abd Algani; B. Kiran Bala (Measurement: Sensors, 2022)
Modern mobile electronic devices such as smartphones or cell phones can now be used for distant devices such as technical systems to monitor and control. While surveillance systems do not require high standards navigating about the time of transfer of the displayed data. More real-time data are needed for a remote mobile robot transfer. Therefore, it has investigated and measured not only the possibilities of employing mobile devices. But also, the supported data transmission channels, such as UMTS, GSM, Wireless LAN, and Bluetooth. The remote-control system is used in many applications such as smart homes, cities, smart hospitals, etc., but it must be today updated to ensure fast-changing technology. Extensive coverage, remote control, and reliable operation in real-time in the deployment of wireless security knowledge. The home automation control system delivers significant features together with a user-friendly interface. A secure remote-based end-to-end security system NTMobile, a technique that enables NAT to provide transverse and encrypted communication from end to end. This confirmed that evaluating the performance of the system in the ECHONET lite compatible smartphone ecosystem. This gives flexibility in configuring time-sensitive industrial networks and enables them to be secured. A safe and reliable remote-control system is also conceivable under the privacy of the user.